2004
DOI: 10.1063/1.1768933
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectrum and stability of a π-type hydrogen-bonded complex between the OH and C2H2 reactants

Abstract: A hydrogen-bonded complex between the hydroxyl radical and acetylene has been stabilized in the reactant channel well leading to the addition reaction and characterized by infrared action spectroscopy in the OH overtone region. Analysis of the rotational band structure associated with the a-type transition observed at 6885.53(1) cm(-1) (origin) reveals a T-shaped structure with a 3.327(5) A separation between the centers of mass of the monomer constituents. The OH (v = 1) product states populated following vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 64 publications
4
52
0
Order By: Relevance
“…A very recent study from Leeds (McKee et al 46 ) measured the temperature and 1015 pressure dependence of the rate coefficient in He over the range 210 -373 K and 5-760 Torr, and also in N 2 and SF 6 at room temperature. A full summary of previous determinations and calculations of k 3 in the literature is given in McKee et al 46 The results yielded the following expression for k 3 A weakly-bound T-shaped OH-C 2 H 2 van der Waals complex has been observed within a supersonic free-jet expansion for which the binding energy was measured to be 11.4 kJ mol -1 , 48 and confirmed by ab initio calculations. 48 The van der Waals complex is likely to be formed without a 1035 activation barrier, and at the low temperatures of the pulsed Laval expansion (down to 69 K in the present work) formation and stabilisation of the complex might be expected to lead to a measurable loss of OH radicals.…”
Section: Measurement Of Rate Coefficients For Oh+c 2 Hmentioning
confidence: 75%
See 1 more Smart Citation
“…A very recent study from Leeds (McKee et al 46 ) measured the temperature and 1015 pressure dependence of the rate coefficient in He over the range 210 -373 K and 5-760 Torr, and also in N 2 and SF 6 at room temperature. A full summary of previous determinations and calculations of k 3 in the literature is given in McKee et al 46 The results yielded the following expression for k 3 A weakly-bound T-shaped OH-C 2 H 2 van der Waals complex has been observed within a supersonic free-jet expansion for which the binding energy was measured to be 11.4 kJ mol -1 , 48 and confirmed by ab initio calculations. 48 The van der Waals complex is likely to be formed without a 1035 activation barrier, and at the low temperatures of the pulsed Laval expansion (down to 69 K in the present work) formation and stabilisation of the complex might be expected to lead to a measurable loss of OH radicals.…”
Section: Measurement Of Rate Coefficients For Oh+c 2 Hmentioning
confidence: 75%
“…However, this was not observed, and so it is concluded that under our conditions the 1040 complex is not formed to a great extent. Lower temperatures (as produced in a free-jet expansion 48 ) or consierably higher densities may be required to stabilise the complex and enable it to be inferred via loss of signal from the OH reagent.…”
Section: Measurement Of Rate Coefficients For Oh+c 2 Hmentioning
confidence: 99%
“…This temperature dependence is subtle compared to OH(v=1,2) + C2H2 where a distinct minimum was observed at ~ 300 K, with ki increasing much more strongly with temperature. This higher temperature minimum for OH(D)/SO2 implies that its vdW complex is slightly more strongly bound than that between OH/C2H2, ~ 10 kJ mol -1 , [41][42] based on the observation that the probability for VET in HCl and HF was seen to go through a minimum at ca. 350 and 1000 K, respectively, where the heats of dimerization are 9…”
Section: Interpretation Of the Results For Oh/od(v=123)mentioning
confidence: 99%
“…[1][2][3] Along the entrance channel to this reaction, a dipole-quadrupole interaction stabilizes a T-shaped, hydrogen bonded complex (OH-C 2 H 2 ), whose zero-point level lies ≈2.7 kcal mol −1 below the separated reactants. 4 Moreover, this entrance channel complex is located behind a barrier ≈1 kcal mol −1 above the reactant asymptote. [4][5][6] The orbital degeneracy of the OH moiety is lifted upon complex formation, and the orbital angular momentum is quenched upon C-O bond formation.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, this entrance channel complex is located behind a barrier ≈1 kcal mol −1 above the reactant asymptote. [4][5][6] The orbital degeneracy of the OH moiety is lifted upon complex formation, and the orbital angular momentum is quenched upon C-O bond formation. Nuclear motion carrying the system from reactants to products, therefore, occurs on two coupled potential surfaces (A ′ and A ′′ ), which are degenerate at long range and distinguished by the orientation of the OH singly occupied pπ orbital.…”
Section: Introductionmentioning
confidence: 99%